2003
DOI: 10.1161/01.res.0000094747.05021.62
|View full text |Cite
|
Sign up to set email alerts
|

AP-1 Is Involved in UTP-Induced Osteopontin Expression in Arterial Smooth Muscle Cells

Abstract: Abstract-Osteopontin (OPN), an RGD-containing extracellular matrix protein, is associated with arterial smooth muscle cell (SMC) activation in vitro and in vivo. Many cytokines and growth factors involved in vessel wall remodeling induce OPN overexpression. Moreover, we recently demonstrated that the extracellular nucleotide UTP also induces OPN expression and that OPN is essential for UTP-mediated SMC migration. Thus, we set out to investigate the mechanisms of OPN expression. The aim of this study was to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…Luciferase and ␤-galactosidase activities were assayed as described previously (15). For each sample, luciferase activity was normalized to ␤-galactosidase activity to compensate for differences in transfection efficiency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Luciferase and ␤-galactosidase activities were assayed as described previously (15). For each sample, luciferase activity was normalized to ␤-galactosidase activity to compensate for differences in transfection efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…The UTP-mediated increase of OPN protein expression results from enhanced gene transcription and stabilization of its transcript (15), but the way chemotactic factors regulate OPN expression remains poorly defined. Vitamin D receptor (16), estrogen receptor ␣ (17), Smad (18), Cbfa (19), and Ets-1 (20) have been shown to regulate OPN expression in osteoclasts, whereas metastasis-associated transcription factor (21), Tcf-1, Ets-1, Ets-2, polyomavirus enhancer A-binding protein-3, c-Jun (22) and acute myeloid leukemia-1 (23) are involved in OPN expression in cancer cells.…”
mentioning
confidence: 99%
“…Previous studies have shown a regulatory function for the AP-1 consensus site located at Ϫ76 bp in the transcriptional regulation of the OPN gene (43)(44)(45). The importance of this AP-1 site for the transcriptional activity of the OPN promoter has been highlighted by a complete loss of basal and inducible OPN promoter activity after site-directed mutagenesis (43)(44)(45).…”
Section: Fxr/shp Directly Regulates Opn Gene Expression On Activated mentioning
confidence: 99%
“…The importance of this AP-1 site for the transcriptional activity of the OPN promoter has been highlighted by a complete loss of basal and inducible OPN promoter activity after site-directed mutagenesis (43)(44)(45). We have previously shown that FXR activation induces a SHP-dependent inhibition of JunD and c-Jun binding to the AP-1 binding site (46,47).…”
Section: Fxr/shp Directly Regulates Opn Gene Expression On Activated mentioning
confidence: 99%
“…Alternatively, dysregulation of OPN may represent a further downstream event following activation of the dioxin receptor, for example, by receptor-mediated negative regulation of the activity of the c-jun/c-fos complex (AP-1; Gillesby et al, 1997;Suh et al, 2002). AP-1 has previously been shown to activate the OPN promoter (Bidder et al, 2002;Denhardt et al, 2003;Renault et al, 2003). As discussed below, in either scenario it will be important to establish a causal link between dysregulation of OPN expression and stomach tumorigenesis.…”
mentioning
confidence: 99%